Effect of planting depth and time on seeds germination of Manna oak (Quercus brantii Lindl.) - Arkan Heydari; Asadollah Mattaji; Hadi Kia-daliri; Naghi Shabanian (تحقیقات جنگل و صنوبر ایران, 2011)
Due to benefits of Quercus brantii Lindl. and its important role in soil and water protection, this species is very important in its environment, especially the Zagros area. Because of over harvesting, the existence of this species is in danger, so its plantation must be considered and its sowing methods must be known. Therefore, this study was carried out in Rykhlan nursery in completely randomized design with unbalanced factorial experiment. Planting depth (4-5 cm and 7-8 cm) and time (December and March) was considered as two treatments with 3 replicates and 40 pots in each replication. Results showed that planting time had significant effect on survival and shoot and root dry weight ratio. Planting depth had significant effect on all factors. Therefore, planting in December with 7-8 cm depth had the best results for all studied factors.